Phosphorylated bacterial cellulose coating material, preparation method and aqueous zinc battery negative electrode

By using phosphorylated bacterial cellulose coating material on the zinc negative electrode of zinc ion battery to form zinc zinc zinc zinc phosphate layer, the problems of dendrites growth and corrosion are solved, and the corrosion resistance and cycle life of the battery are improved.

CN119505604APending Publication Date: 2025-02-25HUBEI UNIV

Patent Information

Application Number
CN202411466358.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Dentite growth and corrosion on the negative electrode of zinc in zinc ion batteries seriously damage the cycle life and safety of the battery.

Method used

The zinc negative electrode is modified by phosphorylated bacterial cellulose coating material, and by forming a layer of zinc organic phosphate, the electrolyte and zinc negative electrode are blocked to inhibit dendrites' growth and corrosion.

Benefits of technology

It significantly improves the corrosion resistance of aqueous zinc ion batteries, extends the shelving life of the battery, and improves the circulation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505604A_ABST
    Figure CN119505604A_ABST
Patent Text Reader

Abstract

The invention relates to a phosphorylated bacterial cellulose coating material, a preparation method and a water-based zinc battery negative electrode, bacterial cellulose is modified by ammonium dihydrogen phosphate and urea to obtain phosphorylated bacterial cellulose, the phosphorylated bacterial cellulose is added with water for dispersion and then dispensed on the surface of a zinc negative electrode, and after drying, the surface of the zinc negative electrode is modified with a phosphorylated bacterial cellulose coating. A layer of organic zinc phosphate can be generated at the junction of the coating and the zinc negative electrode to separate electrolyte from the zinc negative electrode, and meanwhile, phosphorylated fibers have stronger interaction with water molecules, so that the electrolyte can be locked. Therefore, the hydrogen evolution reaction on the surface of the zinc negative electrode and the generation of byproducts are effectively inhibited, the corrosion resistance of the water-based zinc ion battery is enhanced, and the shelf life of the battery is prolonged. Meanwhile, the deposition behavior of zinc ions can be effectively regulated and controlled by the fine network structure of the bacterial cellulose and phosphate groups on the fibers, so that the generation of zinc dendrites is inhibited, and the long cycle life of the water-based zinc ion battery is effectively prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of negative electrodes for aqueous zinc batteries, and in particular to a phosphorylated bacterial cellulose coating material and a preparation method thereof, and a negative electrode for an aqueous zinc battery. Background Art

[0002] With the continuous growth of global energy demand and the improvement of environmental protection awareness, the research and application of sustainable energy storage systems have received extensive attention. As a key electrochemical energy storage device, zinc-ion batteries are considered to be promising candidates for future sustainable energy storage systems due to their high energy density, low cost and environmental protection characteristics. However, zinc-ion batteries face challenges in cycle stability and electrochemical performance, especially the dendrite growth and corrosion phenomena on the zinc negative electrode, which seriously damages the cycle life and safety of the battery.

[0003] Dendrite growth and corrosion on the zinc negative electrode are common problems in zinc-ion batteries. During the charge and discharge process, zinc ions are reduced and deposited on the negative electrode surface to form a metallic zinc layer. However, due to the high electrode potential of metallic zinc, it easily reacts with impurities in the electrolyte, resulting in corrosion of the zinc metal layer and growth of dendrites. These dendrites not only cause internal short circuits in the battery, but also increase the internal resistance, thereby reducing the battery's cycle stability and electrochemical performance.

[0004] In order to solve these problems of zinc anode in zinc-ion batteries, researchers have conducted extensive research on the surface modification of zinc anode. Introducing suitable modified materials onto the surface of zinc anode can enhance the deposition behavior of zinc ions, inhibit the growth of dendrites and corrosion phenomena, and thus improve the cycle stability and electrochemical performance of the battery.

[0005] In the field of surface modification of zinc-ion battery negative electrodes, researchers have adopted a variety of material strategies, including inorganic materials, organic materials, and composite materials. Inorganic materials such as carbon materials, metal oxides, and metal phosphates provide more deposition sites, promote the uniform deposition of zinc ions, and act as conductive networks or catalysts to enhance the electronic transport properties and cycle stability of the battery. Organic materials, including conductive polymers, organic acids, and ionic liquids, further improve battery performance by forming protective films and improving electrolyte properties to reduce the corrosion and dendrite growth of zinc metal. In addition, composite materials utilize the properties of different materials, such as high surface area and good conductivity, to further optimize the deposition behavior of zinc ions and the overall performance of the battery. Together, these modification strategies significantly improve the stability and electrochemical performance of zinc-ion batteries.

[0006] Inorganic coatings are often fragile and unstable, and may irreversibly crack during the electrochemical process due to the volume change of the zinc negative electrode, thereby losing close contact with the negative electrode. Organic coatings often have the problem of increasing the ion transfer impedance inside the battery, resulting in an increase in the internal resistance of the battery and affecting the performance of the battery. Summary of the invention

[0007] The invention provides a phosphorylated bacterial cellulose coating material and a preparation method, and an aqueous zinc battery negative electrode. A layer of organic zinc phosphate is generated by the phosphorylated bacterial cellulose coating material and a zinc negative electrode sheet to separate an electrolyte and the zinc negative electrode. At the same time, the phosphorylated bacterial cellulose has a stronger interaction with water molecules, thereby effectively inhibiting the hydrogen evolution reaction on the surface of the zinc negative electrode and the generation of by-products, thereby enhancing the corrosion resistance of the aqueous zinc ion battery, increasing the shelf life of the battery and improving the cycle performance.

[0008] The solution of the present invention to solve the above technical problem is as follows: a phosphorylated bacterial cellulose coating material, the raw materials of the coating material include bacterial cellulose, diammonium phosphate, and urea.

[0009] Preferably, the mass ratio of bacterial cellulose, diammonium phosphate and urea is 1:1.5-2:7-8. More preferably, the mass ratio of bacterial cellulose, diammonium phosphate and urea is 1:1.6-1.9:7-7.9. More preferably, the mass ratio of bacterial cellulose, diammonium phosphate and urea is 1:1.775:7.33.

[0010] As a type of cellulose, bacterial cellulose has a higher water-locking capacity than other celluloses, can better bind electrolytes, and has better mechanical properties. During the battery cycle, it can effectively prevent the growth of zinc dendrites after the coating breaks. It also has a finer fiber network structure, which can effectively regulate the deposition behavior of zinc ions, uniformly deposit zinc ions on the zinc negative electrode, and prevent the formation of zinc dendrites. Urea is used to promote the swelling of the fiber, thereby increasing the chance of uniform contact between the phosphorylation agent and the fiber. Ammonium dihydrogen phosphate is the source of the phosphate group.

[0011] The method for preparing the phosphorylated bacterial cellulose coating material as described above comprises the following steps:

[0012] 1) dissolving bacterial cellulose in water, mixing the obtained bacterial cellulose dispersion with urea and diammonium phosphate, and drying to obtain a prefabricated solid;

[0013] 2) performing a phosphorylation reaction on the prefabricated solid to obtain a yellow phosphorylated solid;

[0014] 3) After the phosphorylated solid is mixed and dispersed with deionized water, it is washed until the yellow phosphorylated solid becomes a white gel product. After vacuum freeze-drying, the obtained fluffy white solid is the phosphorylated bacterial cellulose coating material.

[0015] Preferably, in step 1), the concentration of the bacterial cellulose dispersion is 0.8 wt %.

[0016] Preferably, in step 2), the phosphorylation reaction temperature is 130-150° C., and the reaction time is 10-40 min. In this temperature range, the phosphorylation process of bacterial cellulose can be kept stable.

[0017] Preferably, in step 3), the phosphorylated solid and deionized water are mixed in a mass ratio of 1:200, and ultrasonic washing is performed until a white gel product is obtained.

[0018] A negative electrode for an aqueous zinc battery comprises a zinc negative electrode sheet, wherein the zinc negative electrode sheet is modified with a phosphorylated bacterial cellulose coating, and the coating is made of the phosphorylated bacterial cellulose coating material as described above.

[0019] Preferably, the thickness of the phosphorylated bacterial cellulose coating is 5-10 μm. If the coating is too thick, it will affect the overall energy density of the battery, and if it is too thin, it will affect the effect of the coating. If the coating is too thin, it will affect the interface resistance effect between the electrode and the electrolyte.

[0020] The method for preparing the negative electrode of the aqueous zinc battery as described above comprises the following steps:

[0021] 1) mixing the phosphorylated bacterial cellulose coating material with water and dispersing them evenly to obtain a phosphorylated bacterial cellulose dispersion;

[0022] 2) Grinding the zinc foil with 1500-grit sandpaper, washing with anhydrous ethanol and drying to obtain a zinc negative electrode sheet;

[0023] 3) The phosphorylated bacterial cellulose dispersion droplets are applied on the zinc negative electrode sheet and dried to obtain the aqueous zinc battery negative electrode.

[0024] Preferably, in step 1), the concentration of the phosphorylated bacterial cellulose dispersion is 0.5 wt%; the amount of the phosphorylated bacterial cellulose dispersion to be applied is 50 to 200 μL·cm -2 The amount of phosphorylated bacterial cellulose dispersion applied by drop coating is proportional to the coating thickness.

[0025] Preferably, in step 3), the drying temperature is 60° C. and the drying time is 6 hours.

[0026] The working principle of the present invention is:

[0027] The phosphorylated cellulose coating has excellent hydrophilicity, which significantly reduces the interfacial resistance between the electrolyte and the Zn negative electrode. The phosphate groups on the coating chelate with zinc ions, allowing Zn 2+ Rapid diffusion achieves uniform nucleation and deposition of zinc ions, better adapts to changes in the electrode surface, maintains close contact, and provides higher ion transmission capacity. During the coating preparation process, the phosphate groups on the fiber structure can initially react with the zinc foil to form a dense organic zinc phosphate layer, which can effectively separate the electrolyte and the zinc negative electrode, while the organic zinc phosphate can efficiently and quickly conduct zinc ions and provide higher ion transmission capacity.

[0028] The beneficial effects of the present invention are:

[0029] (1) The present invention has low cost, simple preparation, good repeatability, good coating uniformity, environmentally friendly raw materials and no pollution. It can also be prepared on a large scale.

[0030] (2) The coating initially reacts with the zinc foil at the interface to form a dense layer of organic zinc phosphate, which blocks the electrolyte and effectively inhibits dendrite growth and interfacial corrosion of the zinc negative electrode.

[0031] (3) The phosphorylated bacterial cellulose coating has excellent hydrophilicity compared to blank zinc and blank bacterial cellulose coating, which significantly reduces the interfacial resistance between the electrolyte and the zinc negative electrode and improves the ion transmission capacity.

[0032] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. The specific implementation of the present invention is given in detail by the following embodiments and their accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of this application. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0034] Figure 1 This is the appearance diagram of the negative electrode of the aqueous zinc battery modified with phosphorylated bacterial cellulose coating in Example 1 before and after the distortion test;

[0035] Figure 2 The surface morphology of the negative electrode of Example 1 and Comparative Example 1 is obtained by scanning electron microscope;

[0036] Figure 3 This is the EDS spectrum element distribution diagram of the negative electrode of Example 1;

[0037] Figure 4is the infrared (IR) curve diagram of phosphorylated bacterial cellulose and bacterial cellulose in Example 1;

[0038] Figure 5 The surface morphology and elemental analysis of the zinc negative electrode after the coating of the negative electrode of the aqueous zinc battery modified with phosphorylated bacterial cellulose coating in Example 1 is stripped off;

[0039] Figure 6 The wettability contact angle test diagram of the negative electrode of Examples 1 to 3 and 2M zinc sulfate electrolyte;

[0040] Figure 7 After assembling a symmetrical button cell with a blank zinc negative electrode of Comparative Example 1 at 5 mA cm -2 、5mAh cm -2 Down cycle performance test;

[0041] Figure 8 Symmetric button cells assembled with the negative electrodes of Examples 1 to 3 were tested at 5 mA cm -2 、5mAh cm -2 Lower cycle performance comparison chart;

[0042] Fig. 9 Symmetric button cells assembled with the negative electrodes of Examples 1, 4, and 5 at 5 mA cm -2 、5mAh cm -2 Lower cycle performance comparison chart;

[0043] Fig.10 The SEM morphology images of the negative electrodes of Example 1 and Comparative Example 1 immersed in 2M zinc sulfate electrolyte for different time periods;

[0044] Fig.11 This is a SEM morphology image of the negative electrode of Comparative Example 2 after being immersed in a 2M zinc sulfate electrolyte for seven days;

[0045] Fig.12 The XRD test results of the negative electrodes of Example 1 and Comparative Example 1 after being immersed in 2M zinc sulfate electrolyte for different time periods;

[0046] Fig.13 This is the XRD test result of the negative electrode of Comparative Example 2 after being immersed in 2M zinc sulfate electrolyte for seven days;

[0047] Fig.14 It is a comparison diagram of the negative electrodes of Example 1, Comparative Example 1 and Comparative Example 2 subjected to Tafel test and linear sweep voltammetry test in a three-electrode system;

[0048] Fig.15 This is a cycle life test diagram of the negative electrode of Example 1 and Comparative Example 1 assembled with a bacterial cellulose separator and then the cycle-standby process is repeated;

[0049] Fig.16 Symmetric button cells assembled with the negative electrodes of Example 1 and Comparative Example 1 were tested at 5 mA cm -2 、5mAh cm -2 Comparison of XRD test results, corresponding optical photos and SEM surface morphology of the zinc negative electrode surface after 50h of down-cycling;

[0050] Fig.17 CE test diagram of zinc-copper half-cells assembled with negative electrodes of Example 1 and Comparative Example 1 after being placed for 30 days;

[0051] Fig.18 This is a comparative test chart of capacity loss after charging and standing for 12 hours for button zinc-iodine full batteries assembled with negative electrodes of Example 1 and Comparative Example 1;

[0052] Fig.19 The volume change test of hydrogen evolution of the soft-package zinc-iodine full battery assembled with the negative electrode of Example 1 and Comparative Example 1 during the storage process and the corresponding optical photos;

[0053] Fig. 20 This is a charge and discharge cycle test diagram of the soft-pack zinc-iodine full battery assembled with the negative electrodes of Example 1 and Comparative Example 1 after being placed for 7 days. DETAILED DESCRIPTION

[0054] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0055] The raw material specifications and sources used in the following examples and comparative examples are as follows:

[0056] 1. Bacterial cellulose: diameter 50-100nm, length about 20μm, reagent grade (manufacturer: Qihong Technology)

[0057] 2. Ammonium dihydrogen phosphate: analytical grade AR (manufacturer: Shanghai Test)

[0058] 3. Urea: analytical grade AR (manufacturer: Shanghai Test).

[0059] 4. Bacterial cellulose membrane: The bacterial cellulose membrane is placed in a hot water bath at 80-95°C for boiling treatment. At the same time, the deionized water is replaced at regular intervals until the cellulose membrane reaches the maximum swelling degree. Subsequently, the treated cellulose membrane is placed in a vacuum freeze dryer for freeze drying. Finally, the obtained membrane is cut into round sheets that meet the battery size and soaked in 2MZnSO 4 The electrolyte is then used for subsequent battery assembly.

[0060] Example 1

[0061] This embodiment provides a phosphorylated bacterial cellulose coating modified aqueous zinc battery negative electrode 1, which is as follows:

[0062] A. Phosphorylated bacterial cellulose coating material, the preparation steps are as follows:

[0063] 1) Grinding the zinc foil, washing it with anhydrous ethanol and drying it, to obtain a pretreated zinc negative electrode sheet.

[0064] 2) Dissolving bacterial cellulose in water, mixing the obtained bacterial cellulose dispersion with urea and diammonium phosphate, and drying to obtain a prefabricated solid; wherein the concentration of the bacterial cellulose dispersion is 0.8wt%; and the mass ratio of the bacterial cellulose, diammonium phosphate, and urea is 1:1.775:7.33.

[0065] 3) The prefabricated solid was placed at 150° C. for a phosphorylation reaction for 30 min to obtain a yellow phosphorylated solid.

[0066] 4) After the phosphorylated solid is mixed and dispersed with deionized water, it is washed until the yellow phosphorylated solid becomes a white gel product. After vacuum freeze-drying, the obtained fluffy white solid is the phosphorylated bacterial cellulose coating material.

[0067] B. Aqueous zinc battery negative electrode, the preparation steps are as follows:

[0068] The phosphorylated bacterial cellulose coating material is mixed with water and dispersed evenly to obtain a phosphorylated bacterial cellulose dispersion with a concentration of 0.5wt%; the phosphorylated bacterial cellulose dispersion is dropwise coated on a zinc negative electrode sheet, and after drying, the thickness of the phosphorylated bacterial cellulose coating is 5μm, thereby obtaining a phosphorylated bacterial cellulose coating-modified aqueous zinc battery negative electrode 1 (denoted as PBC@Zn).

[0069] Example 2

[0070] This embodiment provides a phosphorylated bacterial cellulose coating modified aqueous zinc battery negative electrode 2, and its preparation steps are basically the same as those in Example 1, except that:

[0071] In step 2) of preparing the phosphorylated bacterial cellulose coating material in part A of Example 1, the mass ratio of bacterial cellulose, diammonium phosphate and urea is adjusted to 1:1.6:7.

[0072] Example 3

[0073] This embodiment provides a phosphorylated bacterial cellulose coating modified aqueous zinc battery negative electrode 3, and its preparation steps are basically the same as those in Example 1, except that:

[0074] In step 2) of preparing the phosphorylated bacterial cellulose coating material in part A of Example 1, the mass ratio of bacterial cellulose, diammonium phosphate and urea is adjusted to 1:1.9:7.6.

[0075] Example 4

[0076] This embodiment provides a phosphorylated bacterial cellulose coating modified aqueous zinc battery negative electrode 4, and its preparation steps are basically the same as those in Example 1, except that:

[0077] In the step of the aqueous zinc battery negative electrode in Part B of Example 1, the amount of phosphorylated bacterial cellulose dispersed droplets applied on the zinc negative electrode sheet is reduced, and after drying, the thickness of the phosphorylated bacterial cellulose coating is 3 μm.

[0078] Example 5

[0079] This embodiment provides a phosphorylated bacterial cellulose coating modified aqueous zinc battery negative electrode 5, and its preparation steps are basically the same as those in Example 1, except that:

[0080] In the step of the aqueous zinc battery negative electrode in Part B of Example 1, the amount of phosphorylated bacterial cellulose dispersed droplets applied to the zinc negative electrode sheet is increased, and after drying, the thickness of the phosphorylated bacterial cellulose coating is 10 μm.

[0081] Comparative Example 1

[0082] Only the zinc foil after polishing and cleaning in step 1) of Example 1 is used as the zinc negative electrode sheet.

[0083] Comparative Example 2

[0084] This comparative example provides a bacterial cellulose coating modified aqueous zinc battery negative electrode, the preparation steps of which are basically the same as those of Example 1, except that:

[0085] Instead of using the phosphorylated bacterial cellulose coating material in Part A of Example 1, bacterial cellulose that has not been phosphorylated is used. Water is added to prepare a bacterial cellulose dispersion droplet with a concentration of 0.5 wt % and the droplets are coated on the zinc negative electrode sheet. After drying, the thickness of the bacterial cellulose coating is 5 μm.

[0086] The above examples and comparative examples were tested for morphology, structure, electrochemical performance and cycle rate performance of assembled batteries:

[0087] 1. Modification of phosphorylated bacterial cellulose coating to modify the surface morphology, thickness and element distribution of the negative electrode of aqueous zinc batteries

[0088] Depend on Figure 1As shown, at the macroscopic level, the surface of the zinc negative electrode modified with the phosphorylated bacterial cellulose coating prepared in Experimental Example 1 is smooth without protrusions or depressions. After the twisting test, the coating is still tightly attached to the surface of the zinc negative electrode, showing excellent adhesion stability and mechanical durability.

[0089] Depend on Figure 2 As shown, through scanning electron microscopy (SEM) analysis, it can be observed that the coating prepared in Example 1 exhibits high uniformity, has no cracks on the surface, and has a coating thickness of only 5 μm. Figure 3 The significant phosphorus signal in the coating of Example 1 is shown, indicating the presence of phosphorus. Figure 4 From the infrared spectroscopy (IR) curve shown in Figure 2, we were able to confirm that the phosphate groups had been successfully introduced into the coating structure. Figure 5 In the figure, the surface morphology and EDS element distribution of the zinc negative electrode after the phosphorylated bacterial cellulose coating was stripped off were shown. It can be seen that a relatively dense organic zinc phosphate layer was formed on the surface of the zinc negative electrode. The electrolyte can be effectively isolated from the surface of the zinc negative electrode, thereby significantly inhibiting the corrosion and hydrogen evolution side reaction on the surface of the zinc negative electrode.

[0090] like Figure 6 As shown in the figure, when the ratio of bacterial cellulose, ammonium dihydrogen phosphate and urea is 1:1.75:7.33, Example 1 exhibits the smallest contact angle, indicating that under this ratio, the coating has a good contact angle with 2MZnSO 4 The electrolyte has the strongest retention ability. Accordingly, Example 1 has excellent electrolyte locking ability, which can effectively confine the electrolyte molecules inside the coating, thereby reducing the free flow of the electrolyte on the electrode surface. This efficient electrolyte retention mechanism not only improves the ionic conductivity, but also synergizes with the in-situ formed organic zinc phosphate layer to greatly block the direct contact between the electrolyte and the zinc negative electrode. Therefore, while improving the battery cycle performance, Example 1 also significantly enhances its corrosion resistance, providing an important reference for the design of electrolyte coating materials.

[0091] 2. Performance test and analysis of symmetric battery assembled from phosphorylated bacterial cellulose coating modified aqueous zinc battery negative electrode

[0092] A 2025 model battery shell and a corresponding spring gasket were used, the treated bacterial cellulose membrane was used as a diaphragm, and the phosphorylated bacterial cellulose coating prepared in Example 1 was used as both the positive and negative electrode materials to assemble a symmetrical button cell.

[0093] The negative electrodes provided in Examples 2 to 5 and Comparative Example 1 were also assembled into symmetrical button cells according to the above method.

[0094] like Figures 7-8 As shown, the symmetrical button cells assembled in Examples 1 to 3 are-2 、5mAh cm -2 Under long cycle, the performance of Example 1 is the best, with the most excellent cycle performance (greater than 1200h), while Example 2 is second and Example 3 is the worst, but the cycle life is better than the blank zinc assembled battery of Comparative Example 1. The proportion of phosphorylation reagent in Example 2, Example 1 and Example 3 increases successively, and accordingly, the access amount of phosphate groups also increases, that is, the degree of phosphorylation shows an increasing trend. During the phosphorylation process, the introduction of phosphate groups has a regulatory effect on the mechanical properties of bacterial cellulose materials. Moderate phosphorylation can significantly improve the mechanical strength of the coating, thereby effectively resisting the growth and penetration of zinc dendrites, thereby extending the cycle life of the battery. However, too high a degree of phosphorylation may cause the coating to become more brittle, the mechanical properties to decrease, and it is easy to suffer physical damage during the electrochemical cycle. In addition, the increase in the degree of phosphorylation will enhance the adsorption capacity of the coating for zinc ions, thereby affecting the transmission kinetics of zinc ions. Appropriate phosphorylation can optimize the ion transmission path, while excessive phosphorylation may hinder ion transmission, increase the internal impedance of the battery, and ultimately shorten the cycle life of the battery.

[0095] Therefore, Example 2 and Example 3 were excluded and no longer mentioned in subsequent tests, and the best sample Example 1 was selected for experimental testing.

[0096] like Fig. 9 As shown, the symmetrical button cells assembled in Example 1, Example 4, Example 5 and Comparative Example 1 have an average current of 5 mA cm -2 、5mAh cm -2 By performing long cycles under the conditions of 1, it can be seen that the battery cycle life of Example 1 exceeds 1200h, which is much longer than the cycle life of Comparative Example 1 and Example 4. And the battery of Example 1 has a smaller polarization voltage during the recycling process. This proves that the negative electrode with phosphorylated bacterial cellulose coating can effectively regulate the deposition of zinc ions and effectively avoid the generation and growth of zinc dendrites caused by "dead zinc". In addition, the uneven zinc ion deposition process will induce local charge accumulation and promote the occurrence of tip discharge. These areas become the preferential sites for the growth of zinc dendrites, thereby increasing the risk of battery short circuit.

[0097] Moreover, when the coating thickness is insufficient (Example 4), its mechanical strength and density of the fiber network are not enough to effectively block the penetration of zinc dendrites, and thus cannot effectively prevent the occurrence of short circuits. On the contrary, although an overly thick coating (Example 5) can provide a better physical barrier, it will inevitably sacrifice the battery energy density. Therefore, while ensuring that the performance is not affected, choosing a thinner coating thickness becomes a more reasonable strategy. By comprehensively considering the following key factors: the excellent fiber network structure of bacterial cellulose, the introduction of phosphate groups and the organic zinc phosphate layer formed on the surface of the zinc negative electrode, the regulatory effect of phosphate groups on the zinc ion deposition process, and the appropriate thickness of the coating, this study successfully prepared a phosphorylated bacterial cellulose coating with excellent performance (Example 1). The coating effectively balances mechanical strength, ion transport and electrolyte retention capacity, providing a reliable solution for the stable operation of zinc-based batteries.

[0098] Therefore, Example 4 and Example 5 are excluded and will not be mentioned in subsequent tests, and the best sample Example 1 is selected for experimental testing.

[0099] 3. Anti-corrosion performance test of aqueous zinc battery negative electrode modified with phosphorylated bacterial cellulose coating

[0100] The zinc sheets of Example 1 and Comparative Example 1 were immersed in 2M zinc sulfate electrolyte and tested every seven days to measure the SEM surface morphology and the signal of the byproduct basic zinc sulfate in XRD. Fig.10 As shown, during the immersion process, as time goes by, the surface coating of the zinc sheet of Example 1 remains intact, and basically no basic zinc sulfate by-product is observed, while a lot of by-products are generated on the original zinc surface of Comparative Example 1, and the amount of by-products increases as time goes by. Fig.11 The zinc negative electrode of Comparative Example 2 shown in FIG. 4 After being immersed in the electrolyte for seven days, scanning electron microscopy (SEM) analysis revealed that the surface morphology showed obvious accumulation of corrosion products, and these products were close to penetrating the bacterial cellulose coating.

[0101] Figures 12-13 As shown in the XRD test results, no basic zinc sulfate signal is detected on the surface of the zinc sheet of Example 1 over time, while the basic zinc sulfate signal of Comparative Example 1 is enhanced over time. Similarly, there is a significant basic zinc sulfate signal in Comparative Example 2.

[0102] like Fig.14 As shown, in the three-electrode system, an Ag / AgCl reference electrode and 1M Na 2 SO 4The solution is an electrolyte for Tafel test and LSV test. A lower corrosion current signal and a lower HER hydrogen evolution reaction activity were tested from Experimental Example 1. The results show that the zinc negative electrode with a phosphorylated bacterial cellulose coating prepared in Example 1 has more excellent corrosion resistance. It shows that the phosphorylated bacterial cellulose coating can better inhibit hydrogen ions from obtaining electrons and then hydrogen evolution on the surface of the zinc negative electrode compared to the bacterial cellulose coating. This is because the phosphorylated coating may reduce the adsorption of water molecules on the electrode surface, because water molecules are the main source of hydrogen ions in the electrolyte, and reducing the adsorption of water molecules can directly reduce the concentration of hydrogen ions, thereby inhibiting the hydrogen evolution reaction.

[0103] Fig.15 The button cells assembled with the negative electrodes of Example 1 and Comparative Example 1 were charged at 5 mA cm -2 、5mAh cm -2 The cycle life test is repeated in the following cycle-resting process. It can be seen that the battery of comparative example 1 is damaged at about 300 hours, while the battery of example 1 can reach a cycle life of more than 2000 hours.

[0104] Fig.16 A set of XRD tests and morphology tests were performed on the symmetrical button cells assembled with the negative electrodes of Example 1 and Comparative Example 1 after cycling for 50 hours. It can be seen that compared with the obvious signal of basic zinc sulfate in Comparative Example 1, basically no obvious signal of basic zinc sulfate was observed in Example 1.

[0105] 4. Performance test and analysis of aqueous zinc battery negative electrode modified with phosphorylated bacterial cellulose coating assembled into zinc-copper half-cell

[0106] A 2025 battery case and a corresponding spring gasket were used, the treated bacterial cellulose membrane was used as a diaphragm, the phosphorylated bacterial cellulose coating prepared in Example 1 was used to modify the negative electrode of the aqueous zinc battery, and the copper foil was used as the positive electrode material to assemble a zinc-copper half-cell. The negative electrode provided in Comparative Example 1 was also assembled into a zinc-copper half-cell according to the above method.

[0107] like Fig.17 As shown in the figure, after 30 days of storage, the CE test was performed, and it can be seen that the battery of Example 1 can still maintain a coulombic efficiency of nearly 100% after 30 days of storage, while the curve of Comparative Example 1 is very messy and abnormal, and is damaged in a very short time. This shows that the PBC coating in Example 1 can effectively inhibit the occurrence of corrosion side reactions and greatly extend the shelf life of the battery.

[0108] 5. Assembly and performance test analysis of zinc-iodine full battery

[0109] A self-supporting iodine electrode was used as the positive electrode, the zinc negative electrode sheet modified with the phosphorylated bacterial cellulose coating prepared in Example 1 and the original zinc sheet in Comparative Example 1 were used as the negative electrode, the treated bacterial cellulose membrane was used as the diaphragm, and a 2M zinc sulfate aqueous solution was used as the electrolyte. The whole was assembled in a 2025-type battery shell to form a zinc-iodine button full battery.

[0110] A self-supporting iodine electrode was used as the positive electrode, the zinc negative electrode sheet modified with the phosphorylated bacterial cellulose coating prepared in Example 1 and the original zinc sheet in Comparative Example 1 were used as the negative electrode, the treated bacterial cellulose membrane was used as the diaphragm, a 2M zinc sulfate aqueous solution was used as the electrolyte, and a soft-pack battery heat-sealed film was used as the shell to assemble a soft-pack zinc-iodine full battery.

[0111] Iodine loading of positive electrode: 15.3 mg cm -2 The test voltage range is 0.4V to 1.6V, the test temperature is 25℃, and the test rate is: 5C for button batteries and 0.5C for soft-pack batteries.

[0112] from Fig.18 It can be seen that the button cell was discharged again after being fully charged and left for 12 hours. In this process, the battery of Example 1 only lost 3.36% of its capacity, compared with the 6.88% capacity loss of the original zinc-assembled battery of Comparative Example 1. The storage capacity retention rate was greatly improved.

[0113] like Fig.19 As shown, the soft-pack battery was put aside for experiment and the volume change test of hydrogen evolution was carried out. The results showed that within the first 21 days, the relative volume change of the soft-pack battery of Comparative Example 1 was more significant, but it was still at a low level overall. However, after 21 days, the volume of the soft-pack battery of Comparative Example 1 changed dramatically. After 49 days of shelving, compared with the volume change of about 350% of the soft-pack battery of Comparative Example 1, the volume of the soft-pack battery of Example 1 had almost no significant change. This macroscopic phenomenon can be intuitively observed from the optical photographs of the two groups of soft-pack batteries. The soft-pack battery of Comparative Example 1 showed obvious bulging, while the soft-pack battery of Example 1 remained basically intact. This shows that the phosphorylated bacterial cellulose coating effectively inhibits the hydrogen evolution side reaction between the zinc negative electrode and the electrolyte.

[0114] like Fig. 20 As shown, further, the soft-pack battery that was set aside for 7 days was subjected to a charge and discharge cycle test at a rate of 0.5C. After completing 300 cycles, the soft-pack battery of Experimental Example 1 still maintained a high specific capacity and a coulombic efficiency close to 100%, showing excellent cycle reversibility. In contrast, the soft-pack battery of Comparative Example 1 could not operate normally due to the serious bulging problem.

[0115] Based on the above experimental results, the zinc negative electrode modified with the phosphorylated bacterial cellulose coating prepared in Example 1 of this study exhibited significantly improved anti-corrosion properties. At the same time, this modification strategy also significantly improved the capacity retention rate of the full battery and extended the shelf life of the battery. The phosphorylated bacterial cellulose coating can play an important role in improving the comprehensive performance of zinc-based batteries, especially in terms of shelf anti-corrosion.

[0116] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any ordinary technician in the industry can smoothly implement the present invention as shown in the drawings and described above. However, any equivalent changes, modifications and evolutions made by technicians familiar with the profession without departing from the scope of the technical solution of the present invention using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.

Claims

1. A phosphorylated bacterial cellulose coating material, characterized in that: The raw materials of the coating material include bacterial cellulose, diammonium phosphate and urea; wherein the mass ratio of the bacterial cellulose, diammonium phosphate and urea is 1:1.5-2:7-8.

2. The phosphorylated bacterial cellulose coating material according to claim 1, characterized in that: The mass ratio of the bacterial cellulose, diammonium phosphate and urea is 1:1.6-1.9:7-7.

6.

3. A phosphorylated bacterial cellulose coating material according to claim 2, characterized in that: The mass ratio of the bacterial cellulose, diammonium phosphate and urea is 1:1.775:7.

33.

4. A method for preparing the phosphorylated bacterial cellulose coating material according to any one of claims 1 to 3, characterized in that: The following steps are involved: 1) dissolving bacterial cellulose in water, mixing the obtained bacterial cellulose dispersion with urea and diammonium phosphate, and drying to obtain a prefabricated solid; 2) performing a phosphorylation reaction on the prefabricated solid under high temperature conditions to obtain a phosphorylated solid; 3) The phosphorylated solid is mixed and dispersed with deionized water, and then washed to obtain a gel product, which is then freeze-dried in vacuum to obtain a phosphorylated bacterial cellulose coating material.

5. A phosphorylated bacterial cellulose coating material according to claim 4, characterized in that: In the step 1), the concentration of the bacterial cellulose dispersion is 0.8 wt %.

6. The phosphorylated bacterial cellulose coating material according to claim 4, characterized in that: In the step 2), the phosphorylation reaction temperature is 130-150° C., and the reaction time is 10-40 min.

7. An aqueous zinc battery negative electrode, comprising a zinc negative electrode sheet, characterized in that: The surface of the zinc negative electrode sheet is modified with a phosphorylated bacterial cellulose coating, and the coating is made from the phosphorylated bacterial cellulose coating material according to any one of claims 1-2.

8. The aqueous zinc battery negative electrode according to claim 7, characterized in that: The thickness of the phosphorylated bacterial cellulose coating is 5 to 10 μm.

9. A method for preparing an aqueous zinc battery negative electrode according to any one of claims 7 to 8, characterized in that: The following steps are involved: 1) mixing the phosphorylated bacterial cellulose coating material with water and dispersing them evenly to obtain a phosphorylated bacterial cellulose dispersion; 2) Grinding the zinc foil, cleaning and drying it to obtain a zinc negative electrode sheet; 3) The phosphorylated bacterial cellulose dispersion droplets are applied on the zinc negative electrode sheet and dried to obtain the aqueous zinc battery negative electrode.

10. The method for preparing an aqueous zinc battery negative electrode according to claim 9, characterized in that: In the step 1), the concentration of the phosphorylated bacterial cellulose dispersion is 0.5 wt %, and the amount of the phosphorylated bacterial cellulose dispersion to be applied is 50 to 200 μL·cm -2 .

Citation Information

Patent Citations

  • Titanium dioxide coated biomass charcoal composite anode material and preparation method and application thereof

    CN112520722A

  • Preparation method of dendrite-free zinc anode

    CN114068858A

  • Phosphorylated nanocellulose with high electric charge quantity and preparation method of phosphorylated nanocellulose

    CN116693702A

  • Porous membrane and zinc battery

    JP2020087605A

Cited By

  • Metal negative electrode material with in-situ generated bacterial cellulose protective layer on surface and preparation method of metal negative electrode material

    CN120237188A